2019
DOI: 10.1152/ajpcell.00168.2019
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of osteoclastogenesis by mechanically stimulated osteoblasts is attenuated during estrogen deficiency

Abstract: Osteoporotic bone loss and fracture have long been regarded to arise upon depletion of circulating estrogen, which increases osteoclastogenesis and bone resorption. Osteoblasts from human osteoporotic patients also display deficient osteogenic responses to mechanical loading. However, while osteoblasts play an important role in regulating osteoclast differentiation, how this relationship is affected by estrogen deficiency is unknown. This study seeks to determine how mechanically stimulated osteoblasts regulat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
22
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 32 publications
(27 citation statements)
references
References 86 publications
5
22
0
Order By: Relevance
“…Although membrane-bound RANKL has been shown to be more potent than soluble RANKL [51], the results presented here suggests that under estrogen de cient conditions this may not be the case. In vitro osteoblast-osteoclast studies previously reported an increase in matrix degradation in estrogen de cient groups compared to estrogen treated group [52]. Here we report a signi cant increase in bone resorption through use of bovine bone resorption assays, in estrogen de cient groups compared to estrogen treated groups.…”
Section: Discussionsupporting
confidence: 51%
See 2 more Smart Citations
“…Although membrane-bound RANKL has been shown to be more potent than soluble RANKL [51], the results presented here suggests that under estrogen de cient conditions this may not be the case. In vitro osteoblast-osteoclast studies previously reported an increase in matrix degradation in estrogen de cient groups compared to estrogen treated group [52]. Here we report a signi cant increase in bone resorption through use of bovine bone resorption assays, in estrogen de cient groups compared to estrogen treated groups.…”
Section: Discussionsupporting
confidence: 51%
“…Following 15 days of expansion in α-MEM culture media at 37 °C, OCY454 cells were treated with estrogen (E: 10 nM 17βestradiol) for 6 days. To simulate postmenopausal conditions (ED), we implemented a model that rst accustomed osteocytes to estrogen before a subsequent period where estrogen supplementation was discontinued, known as estrogen withdrawal, based on our previous established postmenopausal model using MC3T3-E1 and MLO-Y4 cells [23,52]. OCY454 cells were treated with 17β-estradiol (10 nM) for 3 days before it was withdrawn from the media for a further 3 days.…”
Section: Estrogen Treatment Regimesmentioning
confidence: 99%
See 1 more Smart Citation
“…Although membrane-bound RANKL has been shown to be more potent than soluble RANKL [59], the results presented here suggests that under estrogen de cient conditions this may not be the case. In vitro osteoblast-osteoclast studies previously reported an increase in matrix degradation in estrogen de cient groups compared to estrogen treated group [60]. Here we report a signi cant increase in bone resorption through use of bovine bone resorption assays, in estrogen de cient groups compared to estrogen treated groups.…”
Section: Discussionsupporting
confidence: 51%
“…Following 15 days of expansion in α-MEM culture media at 37°C, OCY454 cells were treated with estrogen (E: 10 nM 17βestradiol) for 6 days. To simulate postmenopausal conditions (ED), we implemented a model that rst accustomed osteocytes to estrogen before a subsequent period where estrogen supplementation was discontinued, known as estrogen withdrawal, based on our previous established postmenopausal model using MC3T3-E1 and MLO-Y4 cells [27,60]. OCY454 cells were treated with 17β-estradiol (10 nM) for 3 days before it was withdrawn from the media for a further 3 days.…”
Section: Estrogen Treatment Regimesmentioning
confidence: 99%